Answer:
Step-by-step explanation:
(d + 5) + (d + 5) + (d + 5).....combine like terms
3d + 15 <===
Answer: the answer is down bellow
Step-by-step explanation:
x3-10oo Dimensions ft each S.
I think it’s D. (x+6, y-4)
because you go right on the x and down on the y
Answer:
f^-1(x) = x - 2
Step-by-step explanation:
To find the inverse of a function in terms of x and y, you would sway x and y in the function. We can rewrite f(x) = x + 2 as y = x + 2, since f(x) is basically y in a function. The inverse of y = x + 2 would be x = y + 2. Now, solve for y.
x = y + 2
-2 both sides.
x - 2 = y
y = x - 2
The inverse of y = x + 2 would be y = x - 2, so the inverse of f(x) = x + 2 would be f^-1(x) = x - 2 (f^-1(x) means the inverse of f(x)).
f^-1(x) = x - 2
I hope you find this helpful. :)